GRP-182 The Clinical Pharmacist's Impact on the Appropriate Use of Medicines in Elderly Patients. (12th March 2013) - Arnaud, F; Dubois, F; Soulairol, I; Knight, M; Roux, C; Kinowski, JM
Abstract : Background: Adverse effects caused by the treatment are frequent in the elderly and most often result from an inappropriate prescription. Experts have published a list of potentially inappropriate medicines for the elderly (aged 75 and over) [1]. Purpose: To measure the clinical pharmacist's impact on compliance with this reference work. Materials and Methods: Our study was carried out in two units, the infectious and tropical diseases unit (SMIT) and a multi- purpose medicine unit (MEPO) over a 1.5-month period. Drug prescriptions for patients aged 75 and over were analysed in the units after medicines reconciliation by the clinical pharmacist. Conformity with the list of potentially inappropriate medicines (MPIs) was assessed on the optimised medical record (BMO) and the hospital prescription entry. The list of MPIs was divided into three categories of treatment: unfavourable risk/benefit ratio (type 1), questionable effectiveness (type 2) and unfavourable risk/benefit ratio and questionable effectiveness (type 3). When an inappropriate medicine was prescribed, the clinical pharmacist suggested interruption or alternative treatments. Results: Medicines reconciliation was conducted on 32 patients aged 75 and over in the two units (9 in SMIT and 23 in MEPO). Prescription of MPIs were identified for 11 patients (7 in MEPO and 4 in SMIT). The distribution of these MPIs was: 54.5% for type 1, 18.3% for type 2 and 27.2% for type 3. Medicines were stopped (54.5%), switched (18.2%) or continued (27.3%). Conclusions: We found more at-risk patients in MEPO than in the SMIT. In 27.3% of cases, treatments were continued after consulting the doctor and reassessing the risk/benefit ratio and effectiveness. In 72.7% of cases the clinical pharmacist's contribution led to stopping or switching the MPI, confirming his essential role in the compliance with standards. Reference: M.-L. Laroche, F. Bouthier, L. Merle, J.-P. Charmes. La Revue de Médecine Interne, Volume 30, Issue 7, July 2009, pp. 592–601. No conflict of interest.